PEMANFAATAN LIMBAH AMPAS KOPI SEBAGAI MEDIA LUKIS EDUKATIF BAGI ANAK SEKOLAH DI PT. HARTA MULIA - Rifa'i, Mohamad; Ramadhani, Cindy; Prawidya , Lutfi Eka; Umam, Anfaf Al; Hutagaol, Deasy Elisabeth; Syah, Mirza Andrian (Jurnal Abdimas Musi Charitas, 2025)
Purpose: This community service project aimed to introduce the reuse of coffee grounds as an environmentally friendly painting medium to elementary school students. The program was designed to address environmental concerns related to waste mismanagement and to promote creativity through sustainable practices. Design/Methodology/Approach: The activity was conducted by PT Harta Mulia in collaboration with O.G Café as the source of coffee grounds. The coffee grounds were dried for 1–2 days and processed into a painting material. Educational materials on environmental awareness were delivered, followed by a hands-on painting session. The event was held on Sunday, 15 June 2025, from 11:00 to 14:00 WIB at De Karanganjar Agrotourism and involved 30 children aged 7–12 years from several elementary schools. Findings: Participants showed high enthusiasm and successfully created paintings using coffee-based pigments. The activity enhanced children's understanding of environmental issues and demonstrated the potential of waste transformation into artistic expression. Practical Implications: The initiative provided an effective method for environmental education among children and introduced an accessible, low-cost alternative for art materials. It may inspire similar practices in schools or communities aiming to cultivate eco-conscious creativity. Originality/Value: This project combined environmental sustainability with creative education by utilizing an underused waste product. It offered a novel approach to waste reuse, strengthened community engagement, and reflected corporate social responsibility in practice.